DIVERSITY OF BIRDS AND ITS HABITAT CONDITIONS IN WAAI VILLAGE, SALAHUTU DISTRICT, CENTRAL MALUKU REGENCY - Prinslen Tahitu; L. Latupapua; A. Tuhumury (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
Birds are wild animals that are widely used by humans as food, pets, economic needs, and aesthetics. Bird conservation in Indonesia is currently still focused on conservation areas such as nature reserves, wildlife reserves, and national parks. Conservation efforts need to be carried out in other areas, one of which is in community forests. The purpose of this study was to analyze the diversity of bird species and their habitat conditions in the forest of Waai village, Salahutu district, Central Maluku district. The results obtained through the study were that there were 8 bird species consisting of 6 different families. The index of bird species diversity found in the forest of Waai Village, Salahutu District, Central Maluku Regency is H' = 1.77 this value indicates that the diversity of bird species at the study site is moderate. Vegetation conditions which are bird habitats have 11 species of tree level and 18 species of pole level.